Allusions to Mughal urban forms in the monumentality of Chandigarhs capitol complex - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina (Routledge Taylor & Francis Group, 2016)
The formative influence of the Mughal gardens on the urban spaces of the Capitol Complex, Chandigarh is discussed as part of Le Corbusier’s vision in realising new urban symbols to represent an independent India. Corbusier had not only “regionalised” Modernist elements of architectural design but had “modernised” past urban forms by artfully rejecting the traditional gridded patterns and urban traditions such as the Mughal gardens, and transforming them into a dynamic restructuring and interplay of urban forms and spaces. To disassociate the new capital from its Colonial past and to create a new sense of spatial drama symbolising the nation’s hopes for the future, Fatehpur Sikri’s renowned orthogonal and gridded urban plazas with its interconnected courtyards and cloisters, became part of Corbusier’s arsenal of precedents, and these were abstracted and reworked into a new orchestration of urban spaces; and integrated with Modernised concrete architectural forms. The garden archetype and recurring traditional Mughal devices such as the “chattri” and the trabeated terraces allusions were simplified and synthesised with overlapping “spacesbetween-buildings” such as bodies of water, platforms and a series of roofscapes. The influence of the Mughal gardens is again seen in a subsequent project in later years by Corbusier i.e. the unbuilt proposal for the Venice Hospital, whose layout and planning carry similar overtones of overlapping courtyards but fused into a series of outdoor-indoor spaces due to the need to be cognizant of, and sensitive to, the historical fabric and tissue of an existing city.